PROSPECTS FOR EUROPEAN UNION’S MEAT PRODUCTION IN THE CONTEXT OF CURRENT CONSUMPTION CHALLENGES - Elena SOARE; Paula STOICEA; Carina-Andreea DOBRE; Adina Magdalena IORGA; Aurelia-Vasilica BĂLAN; Irina-Adriana CHIURCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Meat is an important element in human nutrition, and its consumption is expected to increase in the coming years in parallel with population growth. However, the livestock sector faces problems related to climate change, animal protection and welfare, and various epizootics, which have decimated livestock. In this context, the article analyses pig, cattle and sheep herds, as well as the production of pig, beef and sheep meat resulting from slaughterhouses in the EU, focusing on the main animal breeders and meat producers, for the period 2018-2022. The results of the study show that the number of pigs, cattle and sheep in the EU decreased during the period under review, as well as the total production of slaughtered meat. The most important pig breeders were Spain, Germany and France, for cattle - France, Germany and Ireland, and for sheep - Spain, Romania and Greece. Among the meat-producing countries stood out: for pork - Spain, Germany and France; for beef - France, Germany and Italy and for sheep meat - Spain, France and Ireland. At the same time, the article presents the perspectives of meat consumption, in the context of the pressures to which the livestock sector is subject and the changes that are manifested in the food preferences of European consumers.